Problemidentifiering och utveckling av plocklagerverksamhet - Apelkvist, Simon; Nilsson, Pontus (My University, 2014)
E2014:063, Ellos was founded in 1947 by Olle Blomqvist and quickly grew into one of the leading mail order businesses in Sweden. Ellos Group is in the current situation Scandinavia’s largest ecommerce company and since 1997 owned by the French holding company Keering. This meant that Ellos became a part of Redcats Nordic along with brands such as La Redoute, Verbaudet , Daxon and others. 2010 started a project with the aim to develop a logistic model for these products. The result was the department Redmap on Ellos that would serve as both a hub and distribution channel for Northern Europe. The goal of Redmap was to increase the availability of goods for brands it the Redcats Group and minimize the lead time. Since startup, the department has shown poor productivity. Ellos Group has therefore requested a study aimed to identify problems in the department and find out suggestions for improvement that will increase productivity. The work has taken place at Ellos in Viared outside Borås. A status report has been developed and has, together with theory, been analyzed. Based on this strategy, several problems and deficiencies have been identified. For the purpose of improving the productivity two concrete suggestions was developed. The first improvement proposal suggests that the current KPIs need to be revised. In addition to this revision, the KPIs need to be used in a clever way along with their work monitoring and control. Improvement Proposal number 2 is about changing the picking methodology for two kinds of articles. These two should be treated as the same item type and should have a common storage area. It will also provide a structural change. For further support of this improvement proposal, a pilot project was implemented. In addition to the proposals, the authors provided Ellos Group with recommendations for further studies. By implementing the suggestions for improvement the authors expect an increase in productivity, which was called for.
Keywords: Övrig industriell teknik och ekonomi; Grundläggande vetenskaper; Hållbar utveckling; Produktion; Transport; Other industrial engineering and economics; Basic Sciences; Sustainable Development; Production; Transport